Trends in collapse risk assessments of terrestrial and wetland ecosystems - Masés-García, Carlos A.; Herrera-Fernández, Bernal; Briones-Salas, Miguel (Instituto de Ecología, A.C., 2021)
Anthropogenic activities threaten more and more the extension and processes of ecosystems. The IUCN Red List of Ecosystems (RLE) is a global standard for assessing their risk of collapse. In this paper, global trends of risk assessments of terrestrial and wetland ecosystems were analyzed through a search for and analysis of publications from 2010 to 2019 that utilized the RLE protocols. Forty-three publications that evaluated 1227 ecosystems: forests (531), scrublands (181), grasslands and herbaceous (212), wetlands (166), coastal (42), and sparsely vegetated or uncommon ecosystems (95) were found. Fifteen criteria were recorded to delimit the ecosystems, highlighting the type of vegetation used as a proxy in all cases. There was a strong variation in the extension of the ecosystems evaluated. Thirty-four variables were identified to define collapse thresholds: one spatial, 15 biotics, and 18 abiotics; vegetation cover change, geographic distribution, and extension were variables of general application. The periods of reliable data for assessing ecosystems range from 12 to 48 years; with them, 50-year periods (past or future) or changes deductied since 1750 were inferred. Ecosystems in "Least Concern" (412) stood out, only two "collapsed" were found, and there was no significant difference between threatened and non-threatened. The assessments analyzed comprised 69 countries, which were conducted at continental, national, and subnational scales. Improvements in the RLE protocols are proposed and key information is provided for the application of ecosystems risk assessment in the future.